UPACARA NGABEN: KONTESTASI MASYARAKAT DAN DAYA TARIK WISATA - Ni Wayan Murniti (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
Ngaben ceremony is tradition of Balinese people that has art and culture aspect as one tourism destination aspect helps the development of tourism in Bali. Ngaben ceremony which is part of Pitra Yadnya and based on Pitra Rna (owing the ancestor) is commonly defined as a funeral ceremony. Ngaben ceremony as a traditional culture that contains element of art has become a tourisms spectacle object for the tourist, besides as a ritual can be said as a tradition that remains being preserved until now. Custom, art and culture from the implementation of Ngaben ceremony can spur local attraction as a spectacle for both local and foreign tourist. However, Ngaben ceremony always connotes extravagance, because without big cost, often Ngaben cannot be done. Therefore, not few people who do Ngaben ceremony within a long time after the death. Ngaben ceremony is often simplified with the goal of the Ngaben ceremony is still reached. Observing the current development in society, the people preferably use uncomplicated technique that is crematorium as means of contestation. Society contestation through ceremony without preserving tradition, culture, art and customary ritual preservation, precisely provides a convenience for the existence of crematorium. Without we realize the desire and the purpose of society to show our life pattern through certain ceremonies tend to lead to consumptive society even hedonic, where with the existence of crematorium does not reduce the significance of the rituals, traditions, customs, cultures, and arts.Keywords: Contestation, Ngaben, Tourism